2006
DOI: 10.1177/000348940611500404
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Auditory Steady-State Responses in Children and Adults with Normal Hearing, Sensorineural Hearing Loss, or Auditory Neuropathy

Abstract: Multiple ASSRs may reliably predict the behavioral threshold in subjects with SNHL and may serve as a valuable objective measure for assessing the hearing threshold across different frequencies in candidates for cochlear implants and children with auditory neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
42
3
16

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 35 publications
10
42
3
16
Order By: Relevance
“…Several studies reported fewer correlations of PTA and ASSR thresholds on the 0.5 kHz frequency (17,7,23) as well as on the 4kHz frequency (21). A possible explanation could be the type of stimulus modulation because instead of amplitude modulation or amplitude and frequency modulation (7,21) this study used the exponential amplitude modulation associated to the modulation of frequency.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several studies reported fewer correlations of PTA and ASSR thresholds on the 0.5 kHz frequency (17,7,23) as well as on the 4kHz frequency (21). A possible explanation could be the type of stimulus modulation because instead of amplitude modulation or amplitude and frequency modulation (7,21) this study used the exponential amplitude modulation associated to the modulation of frequency.…”
Section: Discussionmentioning
confidence: 98%
“…In cases of sensorial hearing losses the thresholds determined by the ASSR has shown strong correlations with behavioral thresholds determined by the Visual Reinforcement Audiometry (VRA) and/or conditioned audiometry (6,11,12,13,14,15,16), as well as by the pure tone audiometry (PTA) (17,18,19,20,21). In what refers to the degree of sensorial hearing loss the studies show weaker correlations with the less severe losses (22,7,23,24).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported no correlation between auditory steady-state response threshold and behavioural threshold for these patients, [2][3][4] and have reported that auditory steady-state response thresholds range from 20 to 70 dB or more around the behavioural thresholds for this population. With such variability, a patient with a moderate hearing loss as determined by auditory steady-state response assessment could potentially have a normal behavioural threshold or a severe hearing loss, or any degree of loss between these two extremes.…”
mentioning
confidence: 52%
“…Esta situación se explicaría por el modelo de activación más amplio en la membrana basilar, así como por el tiempo de viaje aumentado hacia la región apical de la cóclea, donde se detectan los sonidos graves. Además el ruido ambiental puede producir un efecto de enmascaramiento en las frecuencias más bajas 4,[25][26][27][28][29][30] . La frecuencia de modulación (Mf) también podría ser un factor que influye en la respuesta de PEAEE.…”
Section: Tabla 3 Correlaciones Por Frecuencia Y Por Grupo En Relacióunclassified
“…Esta similitud entre ambos umbrales concuerda con los altos índices de correlación descritos anteriormente para el mismo grupo y se corresponde con investigaciones previas 6,23,31 . En el grupo de normoyentes se observaron diferencias mayores que las planteadas por otros autores 20,24,29,33 . Esta discrepancia se puede argumentar por la limitación en el control del ruido ambiental al no realizar el examen de PEAEE en una cámara sonoamortiguada, variable que afectaría en mayor grado a sujetos con mejor nivel auditivo.…”
Section: Tabla 3 Correlaciones Por Frecuencia Y Por Grupo En Relacióunclassified